β-Galactosidase encapsulada em hidrogéis de carragenana, pectina e carragenana/pectina: estudo comparativo e fatores que influenciam na estabilidade e liberação controlada - Silva, Renata Cristina Da (2017)
A few individuals that do not produce β-galactosidase or produce at low scale suffer with intolerance to lactose, which may cause several health problems. In this sense, the supplementation of β-galactosidase is required, however its passage though the gastrointestinal trait may compromise its stability, making it inactive. β-galactosidase (E.C 3.2.1.23) is an enzyme responsible by catalyzing the process of lactose hydrolysis that provides products such as glucose and galactose. The current study investigated the potential of hydrogels of carrageenan, pectin and pectin/carrageenan to encapsulate the β-galactosidase. The hydrogel counts were made by injecting a polymeric solution (carrageenan and/or pectin) containing the enzyme in a salt solution (potassium chloride and/or calcium chloride). The efficiency of encapsulation was evaluated by the spectrophotometric test of specific enzymatic activity using ortho-nitrophenyl-β-D-galactoside (ONPG). The material obtained was characterized by Fourier Transform Infrared Spectroscopy (FTIR), thermogravimetric analysis (TG/DTG), scanning electron microscopy (SEM) and also by the degree of hydrogel swelling in different mediums. The effects of pH, temperature and storage time were also evaluated in terms of the catalytic activity of the free enzyme and those encapsulated in the hydrogels. Moreover, a study on the performance of catalytic activity through the test of controlled release in vitro was conducted. The carrageenan, pectin and hybrid hydrogels presented efficiency of encapsulation of 58.0 ± 1.0, 72.0 ± 1.0 and 77.0 ± 2.0%, respectively. The pectin hydrogel presented the best performance in the pH and temperature tests in relation to the activity of β-galactosidase. However, the carrageenan presented the best stability after three months stored. Regarding the test of controlled release, the carrageenan and pectin hydrogels were 2.0 and 2.4 times, respectively, more efficient than the commercial tablet on releasing the β-galactosidase in vitro. All these tests provided a systematic and comparative study for the three biopolymers prepared to encapsulate the β-galactosidase. Such approach is not often found in the specialized literature.